Pengaruh Kualitas Produk Dan Digital Marketing Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian - Ainul Apriansyah; Rivera Pantro Sukma Silitonga (Panorama Nusantara, 2023)
This research was conducted to determine the effect of product quality and digital marketing on customer satisfaction through purchasing decisions at Three Buns Burger Jakarta. The population in this study are customers of Three Buns Burger Jakarta. The sampling technique used purposive sampling of 120 respondents. Methods of data collection using questionnaires distributed to respondents. While testing the hypothesis includes path analysis with the help of SmartPLS 3.0. The results of this study are product quality has a positive and significant effect on purchasing decisions; product quality has a positive and significant effect on customer satisfaction; product quality has a positive and significant effect on customer satisfaction through purchasing decisions; digital marketing has no significant effect on purchasing decisions; digital marketing has no significant effect on customer satisfaction; digital marketing has no significant effect on customer satisfaction through purchasing decisions; purchasing decisions have a positive and significant effect on customer satisfaction. The coefficient of determination of the purchase decision is 15.5% and customer satisfaction is 31.1%.